Land Covers Change and Its Impact to Carbon Stocks in Ciliwung Watershed - Basuki Wasis; Bambang Hero Saharjo; Hadi Susilo Arifin; Arief Nugroho Nur Prasetyo (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2012)
Land cover changes will affect the ecological condition of the watershed. Currently, the conversion of natural forests into agricultural land has been one of the main causes of deforestation in Indonesia. The changes could give impact to erosion, increased run off and sedimentation, loss of biodiversity, change of micro climate, the release of carbon and Green House Gas (GHG) into the air, etc. This problem has been going on in Watershed Ciliwung. Forest area, as sources of carbon deposits and carbon absorbents, has limited area along with increasing extents of build up areas. Therefore, it’s estimated the ecological changes will be extended, then will affect the amount of carbon stocks in Watershed Ciliwung. The objectives of research are to determine land cover changes during the last twenty years, to analyze actual carbon stocks in watershed Ciliwung, and to analyze the effect of land cover changes in over twenty years of greenhouse gases, especially CO2. This research used three samples plot on each of the existing land cover. Biomass approach was used in order to estimate carbon stock. Changes in carbon stocks were calculated by using interpolation based on the actual carbon stocks in 2011. The research results showed that build up areas was increased 153,36% during twenty years. The highest potencial carbon stocks was found in pines forests, which is 144,99 tons/ha. Over the last twenty years, carbon stocks in watershed Ciliwung is declined 42.329,75 tons carbon or 155.350,182 tons CO2e.